Advances in Mexico in the middle of the Decade of Action for Road Safety 2011-2020 - Martha Híjar; Ricardo Pérez-Núñez; Aarón Salinas-Rodríguez (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze the progress towards the accomplishment of the expected goal in the middle of the Decade of Action for Road Safety 2011-2020 in Mexico and its states. METHODS This is a secondary analysis of road traffic deaths in Mexico between 1999 and 2015. We projected the trend for the period 2011-2020 using a time series analysis (autoregressive integrated moving average models). We used the value of the Aikaike Information Criterion to determine the best model for the national level and its 32 states. RESULTS Mexico is progressing, approaching the proposed goal, which translates into 10,856 potentially prevented deaths in the five-year period from 2011 to 2015. This was due to a decrease in the number of deaths of motor vehicle occupants, as the deaths of pedestrians and motorcyclists were higher than expected. At least one third of the states had values below their goal; although the mortality rate remains unacceptably high in five of them. We identified four states with more deaths than those originally projected and other states with an increasing trend; thus, both cases need to strengthen their prevention actions. CONCLUSIONS The analysis can allow us to see the progress of the country in the middle of the Decade of Action, as well as identify the challenges in the prevention of traffic injuries in vulnerable users. It contributes with elements that provide a basis for a need to rethink both the national goal and the goal of the different states.